Feminization of Poverty: A critical study on the powerlessness of women informal parking attendants in Surabaya - Ridwan, Ahmad (Salasika, 2025)
This study examines the phenomenon of the feminization of poverty through a case study of women informal parking attendants in the city of Surabaya. In the context of urbanization and economic inequality, poor women are increasingly pushed into vulnerable and unprotected sectors of informal labor. The aim of this research is to reveal the socio-economic realities, survival strategies, and structures of power relations faced by these women. Employing a qualitative approach, the study uses case study methods and in-depth interviews with seven primary informants. The findings show that these women work under legally uncertain conditions, shoulder the dual burden of public and domestic labor, and operate within an informal work structure dominated by patron-client relations and symbolic control. Nevertheless, the women also demonstrate agency through spatial negotiations, community solidarity, and survival strategies. The study concludes that the feminization of poverty in urban spaces is not only economic in nature, but also political and cultural. These findings highlight the urgent need for inclusive and gender-sensitive urban policies to ensure social sustainability for marginalized women in urban settings.